Thermogravitational convection of a pseudoplastic nanofluid with varying parameters in an enclosure having a thermally generating wall section - Loenko, Daria S.; Öztop, Hakan Fehmi; Sheremet, Mikhail A. (Wiley-V C H Verlag Gmbh, 2023)
Researching new and optimizing existing methods of cooling electronic devices are the most important tasks in the modern world. Based on this, our work is devoted to the study of the possibility of intensifying the heat removal from a heated element using natural convective energy transport of a pseudoplastic nano liquid in a cavity. The problem is described by unsteady Oberbeck-Boussinesq differential equations and is solved on the basis of the finite difference method. To calculate the effective parameters of a nanofluid, three sets of different models are used, including temperature dependences. The work also studied the effect of nanoparticles' various types and their volume fraction on flow structure and heat transfer. The results showed that the use of copper oxide as nanoparticles and the correlations of Guo et al. and Jang & Choi can lead to intense cooling of the bottom wall heated section.
Keywords: Buoyancy-Marangoni Convection; Power-Law Nanofluids; Heat-Transfer; Natural-Convection; Flow; Channel; Fluids